Degradation of Lithium-Ion Batteries - Leisti, Sasu (My University, 2025)
Lithium-ion batteries (LIBs) are a cornerstone of modern energy storage systems, powering applications ranging from electric vehicles to portable electronics. However, their performance and lifespan are impacted by mechanical and thermal degradation, which pose challenges for their reliability and safety. This literature review explores the key mechanisms of degradation in LIBs, focusing on mechanical stresses such as pressure, vibration, and thermal cycling, and their effects on electrode integrity, separator stability, and casing durability. This thesis also examines mitigation strategies, including materials-based innovations like polymer-brush electrolytes and two-dimensional materials, as well as advanced design and manufacturing improvements such as stack pressure optimization and embedded sensing technologies. Real-time monitoring techniques, including differential thermal voltammetry and predictive hybrid models, are highlighted for their role in early degradation detection and lifespan prediction. Comparative case studies of LIB degradation in electric vehicles and portable electronics illustrate how application-specific stresses influence battery performance. The review concludes with future research directions, emphasizing the need for intelligent regeneration techniques, hybrid modeling approaches, and sustainable recycling practices to address existing gaps. By combining multidisciplinary strategies, LIBs can achieve greater durability, efficiency, and sustainability, ensuring their continued role as a key technology for better energy systems. This thesis underscores the importance of a comprehensive approach to LIB development to meet the growing demands of modern energy applications.
Keywords: Lithium-ion batteries (LIBs), degradation mechanisms, mechanical stress, thermal cycling, electric vehicles (EV), portable electronics, electrode delamination, separator failure, polymer-brush electrolytes, two-dimensional materials (2D materials), thermal management, predictive modeling, battery lifespan, sustainable recycling, energy storage systems.